5-HT2C serotonin receptor blockade prevents tau protein hyperphosphorylation and corrects the defect in hippocampal synaptic plasticity caused by a combination of environmental stressors in mice. (September 2015) - Busceti, Carla Letizia; Pietro, Paola Di; Riozzi, Barbara; Traficante, Anna; Biagioni, Francesca; Nisticò, Robert; Fornai, Francesco; Battaglia, Giuseppe; Nicoletti, Ferdinando; Bruno, Valeria
Graphical abstract: Exposure to multimodal sensory stressors induces an acute increase of hippocampal 5-HTergic neurotransmission through 5-HT2C receptor leading to the activation of GSK-3β with ensuing tau protein hyperphosphorylation. These effects lead to a transient impairment of hippocampal long-term potentiation and spatial memory. Long-term effects of exposure to multimodal sensory stressors induce hippocampal 5-HT depletion. Abstract: Exposure to multimodal sensory stressors is an everyday occurrence and sometimes becomes very intense, such as during rave parties or other recreational events. A growing body of evidence suggests that strong environmental stressors might cause neuronal dysfunction on their own in addition to their synergistic action with illicit drugs. Mice were exposed to a combination of physical and sensory stressors that are reminiscent of those encountered in a rave party. However, this is not a model of rave because it lacks the rewarding properties of rave. A 14-h exposure to environmental stressors caused an impairment of hippocampal long-term potentiation (LTP) and spatial memory, and an enhanced phosphorylation of tau protein in the CA1 and CA3 regions. These effects were transient and critically depended on the activation of 5-HT2C serotonin receptors, which are highly expressed in the CA1 region. Acute systemic injection of the selective 5-HT2C antagonist, RS-102, 221 (2 mg/kg, i.p., 2 min prior the onset of stress), prevented tau hyperphosphorylation and also corrected the defects in hippocampal LTP and spatial memory. These findings suggest that passive exposure to a combination of physical and sensory stressors causes a reversible hippocampal dysfunction, which might compromise mechanisms of synaptic plasticity and spatial memory for a few days. Drugs that block 5-HT2C receptors might protect the hippocampus against the detrimental effect of environmental stressors.